THE EFFICIENCY OF SUN TRACKING SYSTEMS - Taylanov, Nizom; Taylanov, Nizom (Физико-технологического образование, 2022)
The paper considers the effectiveness of the application of tracking systems. It is shown the effectiveness of the use of solar tracking systems, for further application of the results obtained in the design of a software and hardware complex for monitoring and controlling a photovoltaic station